Sex Differences in a Rat Model of Peripheral Neuropathic Pain and Associated Levels of Endogenous Cannabinoid Ligands - Boullon, Laura; Finn, David P.; Llorente-Berzal, Álvaro (Frontiers in Pain Research, 2021)
Chronic neuropathic pain is a major unmet clinical need affecting 10% of the world population, the majority of whom suffer from co-morbid mood disorders. Sex differences have been reported in pain prevalence, perception and response to analgesics. However, sexual dimorphism in chronic neuropathic pain and the associated neurobiology, are still poorly understood. The lack of efficacy and the adverse effects associated with current pharmacological treatments, further underline the need for new therapeutic targets. The endocannabinoid system (ECS) is a lipid signalling system which regulates a large number of physiological processes, including pain. The aim of this study was to investigate sexual dimorphism in pain-, anxiety- and depression-related behaviours, and concomitant alterations in supraspinal and spinal endocannabinoid levels in the spared nerve injury (SNI) animal model of peripheral neuropathic pain. Sham or SNI surgery was performed in adult male and female Sprague-Dawley rats. Mechanical and cold allodynia was tested weekly using von Frey and acetone drop tests, respectively. Development of depression-related behaviours was analysed using sucrose splash and sucrose preference tests. Locomotor activity and anxiety-related behaviours were assessed with open field and elevated plus maze tests. Levels of endocannabinoid ligands and related N-acylethanolamines in supraspinal regions of the descending inhibitory pain pathway, and spinal cord, were analysed 42 days post-surgery. SNI surgery induced allodynia in rats of both sexes. Female-SNI rats exhibited earlier onset and greater sensitivity to cold and mechanical allodynia than their male counterparts. In male rats, SNI induced a significant reduction of rearing, compared to sham controls. Trends for depressive-like behaviours in females and for anxiety-like behaviours in males were observed after SNI surgery but did not reach statistical significance. No concomitant alterations in levels of endogenous cannabinoid ligands and related N-acylethanolamines were observed in the regions analysed. Our results demonstrate differential development of SNI-induced nociceptive behaviour between male and female rats suggesting important sexually dimorphic modifications in pain pathways. SNI had no effect on depression- or anxiety-related behaviours in animals of either sex, or on levels of endocannabinoid ligands and related N-acylethanolamines across the regions involved in the descending modulation of nociception at the time points investigated.